2017
DOI: 10.1016/j.rbmo.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Luteal phase HCG support for unexplained recurrent pregnancy loss – a low hanging fruit?

Abstract: Recurrent pregnancy loss (RPL) is defined by two or more failed pregnancies and accounts for only 1-5% of pregnancy failures. Treatment options for unexplained RPL (uRPL) are limited. Previous studies suggest a link between delayed implantation and pregnancy loss. Based on this, a timely signal for rescue of the corpus luteum (CL) using human chorionic gonadotrophin (HCG) could improve outcomes in women with uRPL. This retrospective cohort study included 98 subjects with uRPL: 45 underwent 135 monitored cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…There is also no consensus on the proposed management of LPD. Besides treating the underlying cause, several therapeutic regimens have been used: ovulation induction, supplemental progesterone, supplemental progesterone and estrogen, and human chorionic gonadotropin 7578. Progesterone supplementation is the most widely used treatment because of its availability, ease of administration, and tolerability.…”
Section: Etiologiesmentioning
confidence: 99%
“…There is also no consensus on the proposed management of LPD. Besides treating the underlying cause, several therapeutic regimens have been used: ovulation induction, supplemental progesterone, supplemental progesterone and estrogen, and human chorionic gonadotropin 7578. Progesterone supplementation is the most widely used treatment because of its availability, ease of administration, and tolerability.…”
Section: Etiologiesmentioning
confidence: 99%
“…One of the most egregious cases of research misconduct in the UK was exposed earlier in the 1990s when the distinguished gynaecologist Malcolm Pearce of St. George's Hospital in London fabricated a report describing the transplantation of an ectopic pregnancy into a patient's uterus to result in a live birth, as well as falsifying a clinical trial on 191 women with polycystic ovarian syndrome suffering from recurrent miscarriage [17]. Despite the high profile nature of Pearce's case at the time and a formal statement from the respective journal declaring that both publications should be withdrawn, the clinical trial report's abstract remained intact on the journal's website for several years and the paper was subsequently cited in several papers as an example of fertility treatment [18][19][20][21][22][23][24][25].…”
Section: Historical Contextmentioning
confidence: 99%
“…Embryonic trophoblast cells secrete human chorionic gonadotropin (hCG), which maintains the corpus luteum function in early pregnancy and plays a key role in implantation and endometrial receptivity [88]. A retrospective cohort study reported that miscarriage rate and time to pregnancy decreased in the 45 pregnant women who underwent 135 monitored cycles without hCG support, compared to 53 pregnant women who underwent 142 cycles with a single injection of mid-luteal hCG [89].…”
Section: Endocrine Effects On Recurrent Pregnancy Lossmentioning
confidence: 99%